Blocked Autophagy by miR-101 Enhances Osteosarcoma Cell Chemosensitivity In Vitro. (9th June 2014) - Chang, Zhiqiang; Huo, Lifeng; Li, Kun; Wu, Yiming; Hu, Zhenming
Abstract : The adjuvant chemotherapy, such as cisplatin, doxorubicin, and methotrexate has significantly improved survival of osteosarcoma patients. However, the chemoresistance which arose with the chemotherapy blocks achieving favorable outcomes for some patients and finally led to relapse or metastatic disease. Studies have shown paradoxical functions of autophagy in tumor development, which has been demonstrated by microRNAs. In the present study, we determined the involvement of autophagy during the chemotherapy of osteosarcoma cell line, U-2 OS, and further determined the regulation of miR-101 on the autophagy in the U-2 OS cells. Results demonstrated that doxorubicin treatment of U-2 OS cells induced significantly high level of autophagy-characteristic acidic vesicular organelles (AVOs), and induced significant autophagy related protein expression in U-2 OS cells. While the miR-101 could significantly reduce the doxorubicin-induced AVOs and block the autophagy related protein expression in U-2 OS cells. Moreover, the autophagy blockage by miR-101 sensitized the U-2 OS cells to doxorubicin treatment. In summary, miR-101 blocks autophagy during the chemotherapy in osteosarcoma cells and enhances chemosensitivity in vitro .